Performance of Super Capacitor as Solar Energy Storage and Electric Tricycle’s Power Source - Loyola, M. C. B.; Buenaflor, M. L. L.; Comia, J. A. M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Recent developments and projects in the Philippines gave way for the introduction of electric tricycles (etrikes) with lithium-ion batteries as its power source and which use the power grid for charging stations. This paper studied the workability of super capacitor as lone substitute to Li-ion batteries for electric tricycles and charging it by means of power from an alternative source that is solar panel. Specifically, this study is aimed to determine the power needed by super capacitor to fully charge, the time of its full charging, and the distance run by electric tricycle. The electric tricycle is assembled using electric bicycle mounted with a passenger side car. The solar panel is mounted on a support which houses charge controller and other accessories. The super capacitor used has a rating of 48 V, 165 F, modular type while the solar panel is rated 100 W. Various tests were conducted such as distance test and charging time test. From test results, the super capacitor employed in this work requires 68 W of solar panel power to become fully charged in more than 6 minutes. The electric tricycle with a fully-charged super capacitor can run up to 600 meters with driver and passenger load of not more than 118 kgs. A remarkable short average charging time, accounted by its high power density, validates that super capacitors are good storage medium for harvesting power from sporadic energy sources. On the other hand, the result for short distance travelled conveys that super capacitors are said to be suitable only for vehicle transportation requiring short distances such as point-to-point transport services.